A review on thermo-physical properties and heat transfer applications of single and hybrid metal oxide nanofluids - W. H., Azmi; S. N. M., Zainon; K. A., Hamid; R., Mamat (Faculty Mechanical Engineering, UMP, 2019)
Nanofluids have been widely explored by various investigators for different types of nanomaterials either the single nanoparticles or hybrid types. This is due to their advantages in thermal properties as well as contribution to the enhancement in the heat transfer performance. Numerous numbers of studies were performed mostly on oxide nanofluids until today. However, the review on oxide nanofluids and their applications is limited. Hence, this paper highlights the most recent development solely on the oxide nanofluids for heat transfer applications. In addition, a comprehensive review is carried out on the recent studies of thermo‑physical properties on oxide nanofluids and their heat transfer applications. The numerical and experimental studies related to forced convection heat transfer using oxide nanofluids were presented. Most of the literatures confirmed the capability of nanofluids to improve the heat transfer performance and simultaneously insignificant increments in pressure drop. Hence, the oxide nanofluids is recommended for applications in various engineering systems.